Action inquiry for investigating knowledge management within social welfare partnerships - Vipin Chauhan; Gillian Ragsdell; Wendy Olphert (2015)
This paper examines critically the research methodology of an ongoing inquiry about knowledge brokering in a UK-based social welfare partnership called Charnwood Connect (CC). CC is a two-year project funded to improve knowledge management amongst advice practitioners and managers, increase interagency collaboration and make local advice services more accessible and resilient. The partnership comprises a number of local social welfare agencies, better known in the UK as “voluntary and community organisations”, the term that will be used in this paper. The partners involved in CC provide a range of advice, information, signposting and support services mainly to marginalised communities on key social welfare issues such as homelessness, unemployment, debt and domestic violence. The first author is employed by CC as its Knowledge Management Officer with lead responsibility for delivering two core knowledge management outputs: an online platform called the Knowledge Hub and a face-to-face networking facility known as the Charnwood Connect Forum. As its methodology, this study is using a variant of action research known as action inquiry. This involves taking a dialogical approach, collaborating with participants and taking action on the issues identified. More critically, in the current context, this involves an amalgam of first-person inquiry (direct observations, dialogue and critical reflection by the first author who is in situ); second person inquiry where the inquirer seeks reactions and feedback from participants (e.g. through discussions, focus groups and interviews) and, third person inquiry where a wider constituency (e.g. service users) can be involved. The paper shares the rationale for using action inquiry in the current context and its strengths and limitations as a methodology for understanding knowledge brokering in partnership arrangements such as CC. It considers the usefulness and validity of action inquiry in social welfare environments where multiple perspectives exist, participant engagement is key, learning in and through action is desired and the inquirer is also a paid practitioner within the subject organisation. The objective of the paper is to reflect critically on the challenges faced by insiders who undertake practice-based research, the issues involved in deploying a methodology that seeks to synchronise research and action, and the lessons that can be drawn from this about knowledge management in social welfare organisations and wider.